Light Chain Deposition Disease Associated With Multiple Myeloma Developing in Late Pregnancy (Iranian Journal of Kidney Diseases, 2018)
Preeclampsia is the most common cause of proteinuria with hypertension during pregnancy. Primary kidney disease and kidney disease secondary to systemic disorders may rarely occur during pregnancy, resulting in proteinuria. A 34-year-old woman was admitted to our hospital with abdominal distention and lower extremity edema. The pregnancy was terminated at the 24th week of gestation due to preterm labor. Even after the delivery, proteinuria and renal deterioration continued to progress. The M-peak was not found on serum and urine protein electrophoresis. The serum free light chains assay showed absolute elevation of lambda chains at 1013.9 mg/L with a decreased kappa to lambda ratio of 0.05. Kidney biopsy revealed light chain deposition disease with lambda light chain deposits on immunofluorescence. Bone marrow examination was compatible with multiple myeloma. To our knowledge, this is the first reported case of light chain deposition disease associated with multiple myeloma during pregnancy.